Hydraulic structures - Novak, Pavel (Spon Press, 2001)
Hydraulic Structures demonstrates to the advanced undergraduate student the design of hydraulic structures in practice. It does this by explaining dam engineering, the design and construction of embankments, dam outlet works and pumping stations.